2019
DOI: 10.2478/fhort-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mycorrhizal fungi in the protection of juniper, rose, yew and highbush blueberry against Alternaria alternata

Abstract: After conducting two-year observations in nurseries in the Małopolska province, Poland, the species of shrubs on which symptoms of discoloration and withering of the leaves/needles and shoots, and sometimes of whole plants, occurred most frequently were selected for further study. The species included juniper (Juniperus horizontalis ‘Wiltonii’, rose (Rosa ‘Star Profusion’), yew (Taxus × media ‘Hillii’) and highbush blueberry (Vaccinum corymbosum ‘Patriot’). The predominant fungus isolated from the diseased pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…It has been reported that AM fungal species applied to strawberries reduced the pathogenicity of R. fragariae [59]. In an experiment with shrubs, it was determined that mycorrhiza application both suppressed the A. alternata pathogen and encouraged the development of plants [60]. In another study, F. mosseae and Trichoderma harzianum were used against the A. alternata in cucumber and a combination of bioagents had a positive synergistic effect on the reduction in disease severity [61].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AM fungal species applied to strawberries reduced the pathogenicity of R. fragariae [59]. In an experiment with shrubs, it was determined that mycorrhiza application both suppressed the A. alternata pathogen and encouraged the development of plants [60]. In another study, F. mosseae and Trichoderma harzianum were used against the A. alternata in cucumber and a combination of bioagents had a positive synergistic effect on the reduction in disease severity [61].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, grafted plants' taxa enriched in the rhizosphere were assigned to guilds ectomycorrhizal and arbuscular mycorrhizal. In roses, arbuscular mycorrhizal colonization stimulates nutrient and water uptake, biomass accumulation, and tolerance to environmental stress (drought and alkaline irrigation) and disease [66][67][68][69][70][71][72][73]. Among the enriched fungal taxa in grafted plants, some Mortierella, Chaetomium, Humicola, Metarhizium, Schizothecium, and Volutella species have been reported to benefit plant growth or health [74][75][76][77][78][79].…”
Section: Grafting Changes the Rhizosphere Microbiome Of Rose Sp 'Nata...mentioning
confidence: 99%
“…Plant and coexisting microbial signal molecules are required to induce particular pathways of endophyte metabolism leading to a balance of sexual to asexual reproduction and biochemical profile modification as well [17][18][19][20]. Moreover, the secondary metabolites are energy-consuming compounds, so endophytes can increase/decrease their production depending on specific needs, like competition with the other microorganisms or host plant communication and protection [9,[21][22][23]. However, some fungal endophytes were shown to produce the desired compounds without a host plant association.…”
Section: Introductionmentioning
confidence: 99%